PERAN PEMENTASAN DRAMA DALAM MENINGKATKAN KOMUNIKASI DAN KEPERCAYAAN DIRI SISWA - Maranti Oktaviani (Prakata: Jurnal Bahasa dan Sastra Indonesia Serta Pembelajaran, 2025)
Drama performances are an effective learning method in improving students' communication skills and self-confidence. Through drama performances, students can learn to speak in public, express their ideas, and interact with others more confidently. Apart from that, drama performances can also help students develop social skills, such as working together in groups, respecting other people's opinions, and resolving conflicts well. Through drama performances, students can develop social and emotional skills that are critical to their future success. They can learn to work together in a team, respect other people's opinions, and express themselves more effectively. Apart from that, drama performances can also be a means of increasing a sense of solidarity and togetherness among students, thereby creating a more positive and inclusive learning environment